Kajian Efisiensi Energi Proses Penyulingan Dan Sifat Fisik Hasil Penyulingan Minyak Serai Dapur Menggunakan Tungku Sekam Dan Heating Mantel - Rohaeti, E.; Pamungkas, N. G.; Irzaman, Irzaman (BERKALA FISIKA, 2010)
Essential oil distillation has been carried out from the lemongrass material using two heaters there are rice husk and heating mantel. In comparison ingredients (lemongrass: water = 0.125 kg: 0.5 liters) distillation with rice husk heater requires energy 6022.5 kcal, 3660 second distillation time, costs Rp 912.5 with an average rendemen of oil produced 0.0635 %. Distillation with the same material amount using heating mantel requires the energy 832.143 Kcal, distillation time 6990 seconds, the cost Rp 608.6 and producing the rendemen 0.114%. Distillate debit is influenced by the heat generated which produced by the rice husk and heating mantel. The quality of lemongrass oil which produced by the rice husk heating is better than the heating mantel in term of the lemongrass oil color and oil refractive index. Lemongrass oil which is produced by the pale brown of heating rice husk and refractive index values were in the range of 1.4830 to 1.4890. Keywords: rice husk, heating mantel, distillation, lemongrass oil, energy.